Leather squeezing efficiency analysis - Hurramov Shukhrat; Bektoshev Kuvondar; Buriev Eshmurod; Kurbanova Nigora (E3S Web of Conferences, 2024)
This paper presents the results of an efficiency analysis on the pressing of leather after dyeing, determined by the residual moisture content of the leather. The study establishes the law of changes in humidity during the leather pressing process. It was found that as the thickness and initial moisture content of the skin decreases, its final moisture content also decreases. An analytical dependence of the residual moisture content of the skin has been derived, which can be used to determine rational parameters for squeezing machines. The results show that reducing the skin thickness and increasing the roller radius lead to a decrease in the residual moisture content of the leather.